Inhibition of Multiple Protective Signaling Pathways and Ad.5/3 Delivery Enhances mda-7/IL-24 Therapy of Malignant Glioma - Hamed, Hossein A (Nature Publishing Group, 2010)
We have explored the mechanism by which inhibition of multiple cytoprotective cell-signaling pathways enhance melanoma differentiation-associated gene-7/interleukin-24 (mda-7/IL-24) toxicity toward invasive primary human glioblastoma multiforme (GBM) cells, and whether improving adenoviral infectivity/delivery of mda-7/IL-24 enhances therapeutic outcome in animals containing orthotopic xenografted GBM cells. The toxicity of a serotype 5 recombinant adenovirus to express MDA-7/IL-24 (Ad.5-mda-7) was enhanced by combined molecular or small molecule inhibition of mitogen-activated extracellular regulated kinase (MEK)1/2 and phosphatidyl inositol 3-kinase (PI3K) or AKT; inhibition of mammalian target of rapamycin (mTOR) and MEK1/2; and the HSP90 inhibitor 17AAG. Molecular inhibition of mTOR/PI3K/MEK1 signaling in vivo also enhanced Ad.5-mda-7 toxicity. In GBM cells of diverse genetic backgrounds, inhibition of cytoprotective cell-signaling pathways enhanced MDA-7/IL-24–induced autophagy, mitochondrial dysfunction and tumor cell death. Due partly to insufficient adenovirus serotype 5 gene delivery this therapeutic approach has shown limited success in GBM. To address this problem, we employed a recombinant adenovirus that comprises the tail and shaft domains of a serotype 5 virus and the knob domain of a serotype 3 virus expressing MDA-7/IL-24, Ad.5/3-mda-7. Ad.5/3-mda-7 more effectively infected and killed GBM cells in vitro and in vivo than Ad.5-mda-7. Future combinations of these approaches hold promise for developing an effective therapy for GBM.